Analisis Implementasi dan Keberlanjutan Bisnis Takonesian di Kota Palembang - Halery, Alda Antonia Calista; Wijaya, Muhammad Rezki Arangga; Ariani, Nova; Kasih, Yulizar (Universitas Multi Data Palembang, 2025)
This research aims to analyze the implementation and sustainability of a food business that combines Indonesian and foreign cultures. Takonesian is a business operates in food sector. This business offers 3 menu variants that are innovations of takoyaki, which originally used flour but now uses rice as the base. The area analysis in this research focuses on the analysis of marketing mix strategy, business performance analysis (financial reports), and business consideration analysis. Based on the results of the analysis obtained, it can be stated that Takonesian business can be implemented and sustainable.